Altered dendritic morphology of Purkinje cells in Dyt1 ΔGAG knock-in and purkinje cell-specific Dyt1 conditional knockout mice. - Lin Zhang; Fumiaki Yokoi; Yuan-Hu Jin; Mark P DeAndrade; Kenji Hashimoto; David G Standaert; Yuqing Li (PLoS ONE, 2011)
DYT1 early-onset generalized dystonia is a neurological movement disorder characterized by involuntary muscle contractions. It is caused by a trinucleotide deletion of a GAG (ΔGAG) in the DYT1 (TOR1A) gene encoding torsinA; the mouse homolog of this gene is Dyt1 (Tor1a). Although structural and functional alterations in the cerebellum have been reported in DYT1 dystonia, neuronal morphology has not been examined in vivo.In this study, we examined the morphology of the cerebellum in Dyt1 ΔGAG knock-in (KI) mice. Golgi staining of the cerebellum revealed a reduction in the length of primary dendrites and a decrease in the number of spines on the distal dendrites of Purkinje cells. To determine if this phenomenon was cell autonomous and mediated by a loss of torsinA function in Purkinje cells, we created a knockout of the Dyt1 gene only in Purkinje cells of mice. We found the Purkinje-cell specific Dyt1 conditional knockout (Dyt1 pKO) mice have similar alterations in Purkinje cell morphology, with shortened primary dendrites and decreased spines on the distal dendrites.These results suggest that the torsinA is important for the proper development of the cerebellum and a loss of this function in the Purkinje cells results in an alteration in dendritic structure.